Challenges and critical success factors of the application of lean in agile software delivery - Lian, Yuen-Chi (2018)
In the last decade, the growth of internet and information technology has moved the world at a speed That it has never been seen before, forcing many organisations to adopt agile software delivery (ASD) Methods to deliver with lower cost software products with higher quality in a shorter time frame. These organisations have recently introduced lean to further their efforts to become more efficient and deliver better products. This study conducted literature review on ASD and the application of lean in ASD, and collected data from practitioners through interviews and internet survey. The adoption of lean in these organisations were analysed, including the challenges they faced and the Critical success factors for its adoption. As a conclusion, organisations are urged to set out a vision of a learning organisation and prioritise for training to ensure proper understanding, leading to successful adoption of lean.